2021
DOI: 10.1111/are.15196
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance and health of juvenile tambaqui, Colossoma macropomum , in a biofloc system at different stocking densities

Abstract: Biofloc systems (BFT) are considered environmentally friendly as they operate with minimal water use, which is enhanced by the performance of specific microbial communities effective in controlling nitrogen by-products that are potentially toxic to animals (Avnimelech, 1999). Currently, production technologies in BFT have been made available mainly for shrimp (Litopenaeus vannamei) (Ferreira et al. 2020) and Nile tilapia (Oreochromis niloticus) (Cao et al., 2020).Despite prospects for the viability to produce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 39 publications
7
15
0
Order By: Relevance
“…The better production performance of BFT treatments was probably due to nutrient types, the nutritional value of bio oc, and better water quality, as implied in other reports (Azim and Little 2008; Khanjani and Shari nia 2020). So, the resultant data in the present study has pointed out that O. pabda can adapt to BFT based aquaculture system.Regarding stocking density in uence on sh production systems as previously reported(Haridas et al 2017;dos Santos et al 2021), the present study also demonstrated that the BFTS 1 had higher weight gain, SGR and survival compared to the BFTS 2 and BFTS 3 tanks. These ndings corroborate the previous works reporting decreased weight gain of Tambaqui and GIFT Tilapia in a BFT with increasing densities (dosSantos et al 2021;Haridas et al 2017).…”
supporting
confidence: 85%
See 1 more Smart Citation
“…The better production performance of BFT treatments was probably due to nutrient types, the nutritional value of bio oc, and better water quality, as implied in other reports (Azim and Little 2008; Khanjani and Shari nia 2020). So, the resultant data in the present study has pointed out that O. pabda can adapt to BFT based aquaculture system.Regarding stocking density in uence on sh production systems as previously reported(Haridas et al 2017;dos Santos et al 2021), the present study also demonstrated that the BFTS 1 had higher weight gain, SGR and survival compared to the BFTS 2 and BFTS 3 tanks. These ndings corroborate the previous works reporting decreased weight gain of Tambaqui and GIFT Tilapia in a BFT with increasing densities (dosSantos et al 2021;Haridas et al 2017).…”
supporting
confidence: 85%
“…So, the resultant data in the present study has pointed out that O. pabda can adapt to BFT based aquaculture system.Regarding stocking density in uence on sh production systems as previously reported(Haridas et al 2017;dos Santos et al 2021), the present study also demonstrated that the BFTS 1 had higher weight gain, SGR and survival compared to the BFTS 2 and BFTS 3 tanks. These ndings corroborate the previous works reporting decreased weight gain of Tambaqui and GIFT Tilapia in a BFT with increasing densities (dosSantos et al 2021;Haridas et al 2017). Furthermore, the stocking density has such FCR variation which might be related to microbial akes on sh health as well as energy expenditure for the food competition.…”
supporting
confidence: 85%
“…In nature, the fish species C. macropomum, Piaractus brachypomus, and Piaractus mesopotamicus go through long periods of feed restriction, and protocols of feed restriction in captivity have demonstrated improved growth performance [32][33][34][35] and reduced production cost with lower labor and feed cost [36][37][38]. Although the growth performance of juvenile C. macropomum in BFT systems has been described [39][40][41], the physiological condition and growth performance of C. macropomum during BFT maturation and when submitted to different feeding regimes with restriction in BFT have yet to be evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…The search for aquaculture systems that mitigate environmental impacts and improve productivity has increased worldwide (FAO, 2022). Bio oc technology (BFT) is noteworthy in this regard, resulting in increased productivity, as it allows for a higher number of animals to be reared per cubic meter (Haridas et al, 2017;Dos Santos et al, 2021). The BFT system also generates lower amounts of e uent, as it allows for water reuse, due to microorganism nutrient cycling (Martínez-Córdova, et al, 2016; Vadhel et al, 2020;Dos Santos et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, assessments on the possibility of reducing protein levels combined with the best use of natural food, enzymatic activity optimization and nutritional bio oc pro les in BFT systems, as well as the farmed species, comprise important indicators. The feeding habits of species reared in these systems must also be considered, as lterers are preferable, since they are able to make use of bio oc nutritional advantages (Xu and Pan, 2012;Cavalcante et al, 2017;Dos Santos et al, 2021). Within the Brazilian aquaculture scenario, the tambaqui Colossoma macropomum is a native species with high potential in BFT rearing systems, as it displays adequate biological characteristics and signi cant economic importance.…”
Section: Introductionmentioning
confidence: 99%